PENGARUH JUMLAH ZAKAT PRODUKTIF, UMUR PRODUKTIF, JUMLAH TANGGUNGAN, DAN PENGAWASAN TERHADAP PRODUKTIVITAS USAHA (SURVEY PADA MUSTAHIK KABUPATEN PIDIE) - Assafriani Assafriani; Meutia Fitri (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2020)
This study aims to determine the influence of productive zakat amount, productive age, dependents of mustahik, and controll towards productivity of mustahik reaching. This research is conducted by taking samples of mustahik who earn productive zakat from Baitul Mal Pidie and chosen sample for 53 mustahik. The data and information collection used in this study was documentation technique. The data used was the secondary data which directly collected from Baitul Mal Pidie. The testing of independent variable influence toward the dependent variabel used this study was multiple regression model by using SPSS 23.The result of the reseach shows that simultaneously productive zakat amount,productive age, dependents of mustahik, and control have an effect productivity of mustahik reaching. However partially only variable productive zakat amount and controll that effect the productivity of mustahik reaching. Productive age and dependents of mustahik are not affect the productivity of mustahik reaching